Thermoresistive multilayer mirrors antidiffusion barriers for work at the wavelengths 40-50nm - Voronov, Dmitriy L.; Zubarev, Evgeniy N.; Kondratenko, Valeriy V.; Penkov, Alexey V.; Pershin, Yuriy P.; Ponomarenko, Alexander G.; Artioukov, Igor A.; Vinogradov, Alexander V.; Uspenskii, Yuriy A. (American Institute of Physics, 2002)
To improve the thermal stability of Si/Sc multilayer mirrors, thin layers of W were deposited at interlayer boundaries. Using X-ray scattering and transmission electron microscopy, we studied the interaction of Si and Sc layers at elevated temperatures. It was shown that the W layers of 0.5-0.8 nm thickness form dense WSi2 barriers, which prevent a direct contact between Si and Sc and greatly slow down the formation of scandium silicides. Presented measurements show that Si/W/Sc/W multilayers fabricated by de-magnetron sputtering possess long thermal stability up to 250° C and the normal incidence reflectivity of 24 %.
Keywords: thermal stability of Si/Sc; multilayer mirrors; X-ray scattering; термічнf стабільнsстm Si/Sc; багатошарові дзеркала; pозсіювання рентгенівських променів